Sulfurization temperature effects on the growth of Cu2ZnSnS4 thin film - Yoo, Hyesun; Kim, JunHo; Zhang, Lixin (Current applied physics, 2012)
We made Cu2ZnSnS4 (CZTS) thin films by sulfurization of Cu/Sn/Cu/Zn metallic films. Sulfurizations were carried out under different thermal annealing conditions, where maximum temperatures were 440 °C (LT-CZTS) and 550 °C (HT-CZTS). For LT-CZTS films, secondary phases such as SnS2 and Cu2−xS were observed, whereas for HT-CZTS films secondary impurities were not detected. Chemical composition of LT-CZTS film was observed to be very non-uniform. Highly Sn-rich and Zn-rich regions were found on the film surface of LT-CZTS. However, averaged chemical composition for larger area was close to stoichiometry. The HT-CZTS film showed homogeneous structural and chemical composition features. But, for HT-CZTS film, the Sn composition was observed to be decreased, which was due to the Sn-loss. By UV–Visible spectroscopy, optical band gaps of LT- and HT-CZTS films were measured to be ∼1.33 eV and ∼1.42 eV, respectively. The band gap of LT-CZTS film was also observed to be smaller by photoluminescence measurement. The depressed band gap of LT-CZTS film may be ascribed to some defects and low band gap impurities such as Cu2SnS3 and Cu2-xS in the LT-CZTS film. ► Two different CZTS films were made by sulfurization of Cu/Sn/Cu/Zn metallic films, where one (LT-CZTS) was sulfurized at 440 °C and the other (HT-CZTS) at 550 °C. ► The band gaps of LT-CZTS and HT-CSTS were observed to be ∼1.33 eV and ∼1.42 eV, respectively. ► The lower band gap for LT-CZTS is attributed to secondary phases with low band gaps such as Cu2SnS3 and Cu2–xS and possible defects.